Russian Federation : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This Selected Issues paper for the Russian Federation discusses existing empirical efforts to measure the determinants of cross-country financial integration. Empirical studies that have adopted the gravity-model framework have found that it is generally successful in explaining bilateral financial flows. If the pension gap were to be financed through the budget, the model simulations suggest that fiscal room is best created by lowering government consumption. Consideration should be given to outsourcing the management of the mandatory contributions to private asset managers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet